Focus : customs brokers - an overview of the outcomes of the WCO study report (2016)
Reviews members' practices and is based on the results of a survey and research carried out by the WCO Secretariat. Provides some policy and organisation considerations to serve as a reference point for Customs administrations who are looking at the establishment or adjustment of a licensing / regulatory regime for brokers.
Keywords: CUSTOMS